The first experience of extensive liver resections in infants at the National Children’s Medical Center (Herald of the National Children's Medical Center, 2024)
Background. We aimed to analyze the initial cases of major right-sided hepatectomies in infant patients for various neoplasms performed at our center.Materials and methods. We aimed to analyze the initial cases of major right-sided hepatectomies in infant patients for various neoplasms performed at our center.Results. The mean age of patients was 7.3 months. Indications for liver resection were hepatoblastoma in two cases and anastomosing hemangioma in one case. Two patients underwent anatomical resection of the right hepatic lobe, and one patient underwent extended right-sided hepatectomy. The mean operation time was 230 minutes. The average blood loss was 133 ml. No surgical complications were observed in patients. The mean hospital stay after surgery was 7.3 days. Patients diagnosed with hepatoblastoma received postoperative chemotherapy courses. No recurrence of neoplasms was detected during the observation period.Conclusion. The initial results of liver resection surgery at our center have demonstrated the feasibility and safety of performing radical major hepatectomies in pediatric patients with large liver neoplasms. These outcomes are comparable to the global literature. Performing such operations in infants necessitates substantial expertise in hepatobiliary surgery on the part of the operating surgeon. Patients with hepatoblastoma require post-hepatectomy chemotherapy according to oncologists’ recommendations. There is a need to develop primary outpatient services for liver tumor screening and timely diagnosis in pediatric patients.
Keywords: liver resection; major hepatectomy; pediatric surgery; oncology